2019
DOI: 10.1128/jvi.00296-19
|View full text |Cite
|
Sign up to set email alerts
|

Specificity of Plant Rhabdovirus Cell-to-Cell Movement

Abstract: Positive-stranded RNA virus movement proteins (MPs) generally lack sequence-specific nucleic acid-binding activities and display cross-family movement complementarity with related and unrelated viruses. Negative-stranded RNA plant rhabdoviruses encode MPs with limited structural and functional relatedness with other plant virus counterparts, but the precise mechanisms of intercellular transport are obscure. In this study, we first analyzed the abilities of MPs encoded by five distinct rhabdoviruses to support … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 91 publications
(127 reference statements)
2
28
0
Order By: Relevance
“…Previous studies with the CoRSV MP localized the protein predominantly at the cell periphery when ectopically expressed in plant cells ( Ramalho et al, 2014 ). MP nuclear localization has also been reported for the lettuce necrotic yellows cytorhabdovirus (LNYV), alfalfa dwarf cytorhabdovirus (ADV), and SYNV betanucleorhabdovirus ( Goodin et al, 2002 , 2007 ; Martin et al, 2012 ; Bejerman et al, 2015 ; Zhou et al, 2019 ). For the LNYV MP (4b protein), its nuclear localization was supported by the presence of a predicted NLS domain, whereas no canonical NLS was predicted for ADV MP (P3 protein).…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…Previous studies with the CoRSV MP localized the protein predominantly at the cell periphery when ectopically expressed in plant cells ( Ramalho et al, 2014 ). MP nuclear localization has also been reported for the lettuce necrotic yellows cytorhabdovirus (LNYV), alfalfa dwarf cytorhabdovirus (ADV), and SYNV betanucleorhabdovirus ( Goodin et al, 2002 , 2007 ; Martin et al, 2012 ; Bejerman et al, 2015 ; Zhou et al, 2019 ). For the LNYV MP (4b protein), its nuclear localization was supported by the presence of a predicted NLS domain, whereas no canonical NLS was predicted for ADV MP (P3 protein).…”
Section: Discussionmentioning
confidence: 86%
“…Our findings reveal that dichorhavirus MPs do not display cross-movement complementation with distinct (+) RNA viruses, suggesting either that these MPs mediate virus transport with a mechanism distinct from those viruses used in the transport complementation assay or the requirement of specific interactions and/or proteins playing a role in virus transport. For plant rhabdoviruses and others (-)ssRNA viruses, their MPs were able to rescue the cell-to-cell movement of potexvirus, tobamovirus, or alfamovirus defective-movement mutants ( Huang et al, 2005 ; Peiro et al, 2014a ; Mann et al, 2016 ; Leastro et al, 2017b ; Zhou et al, 2019 ). On the other hand, defective nucleo- and cytorhabdovirus movement mutants were rescued only by their cognate MPs ( Zhou et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, both RYSV M and ODC1 interact with the same ODC-binding domain at the C-terminus of OAZ1. During the propagation of the nucleorhabdoviruses in the nuclei of insect vectors and plant hosts, the RNP cores are assembled within the viroplasm matrix in the nucleic, and then M proteins recognize and condense RNP cores to assemble the bullet-shaped or ba- cilliform non-enveloped virions at the nuclear membrane (Wang et al, 2018;Jackson and Li, 2016;Jackson et al, 2018;Zhou et al, 2019). Our electron microscopic observation has shown that abundant non-enveloped bulletshaped virions of RYSV budded from the nuclear membrane into the cytoplasm in the CNS of N. cincticeps (Wang et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The genome of SYNV contains six open reading frames (ORFs) in the order 3’-N-P-sc4-M-G-L-5’ that are conserved among plant rhabdoviruses ( Jackson et al, 2005 ). The N, P, L proteins form a ribonucleoprotein complex with the viral genomic RNA that is essential for replication and transcription ( Ganesan et al, 2013 ; Wang et al, 2015 ), and the M and G proteins are involved in virus budding and morphogenesis ( Sun et al, 2018 ), whereas the sc4 protein is the cell-to-cell movement protein ( Zhou et al, 2019 ). Several genetic features of rhabdovirus make their genomes highly amenable for vector engineering.…”
Section: Introductionmentioning
confidence: 99%